Functional polymorphisms in the FCN2 gene are not associated with invasive pneumococcal disease. - Chapman, S; Vannberg, F; Khor, C; Segal, S; Moore, C; Knox, K; Day, N; Davies, R; Crook, D; Hill, A (2007)
L-ficolin is a pattern-recognition molecule which binds lipoteichoic acid and Gram-positive bacteria and activates the lectin pathway of complement. Five common functional polymorphisms have recently been identified in the FCN2 gene which encodes L-ficolin: three promoter polymorphisms (at positions -986, -602 and -4) which affect serum L-ficolin concentration, and two non-synonymous polymorphisms (Thr236Met and Ala258Ser) which influence carbohydrate binding. We studied the frequencies of these polymorphisms in individuals with invasive pneumococcal disease (IPD) and a control group. Although the five FCN2 polymorphisms were each present in the UK Caucasian population studied, no significant associations were observed between the FCN2 polymorphisms and susceptibility to IPD. This is in contrast to mannose-binding lectin deficiency, which we have previously shown to be associated with increased susceptibility to IPD. Although we are unable to exclude small effects of FCN2 genetic variation on susceptibility to IPD, the result suggests that L-ficolin may not be critical for host defence against pneumococcal infection.